Creep and depinning of vortices in nontwinned YBa2Cu3O6.87 single crystal - Bondarenko, A.V.; Zavgorodniy, A.A.; Lotnik, D.A.; Obolenskii, M.A.; Vovk, R.V.; Biletskiy, Y. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
We present the results of transport study of vortex dynamics in YBa2Cu3O6.87 crystals in the magnetic field H||c. In low magnetic fields, H < 4 kOe, the measurements were performed in the range of vortex velocities n=10-4–2 m/s, which covers thermal creep and flux flow modes. The pinning force Fp nonmonotonically depends on magnetic field in both modes, though low-field minimum in the Fp(H) curve shifts to higher fields with increased velocity n, that is interpreted as partial ordering the vortex lattice. The increase of the pinning force Fp upon increasing the field, which is observed in the flux flow mode in fields H ≥ 3 kOe, is interpreted by presence of finite transverse barriers. The barriers result in preserving the entangled vortex solid phase for the above-barrier vortex motion along the action of the Lorentz force. We also show that field variation of the depinning current has a single maximum, while field variation of the pinning force inside deep creep mode has two maxima. Appearance of two maxima is associated with nonmonotonous field variation of the activation energy Upl, which corresponds to plastic vortex creep mediated by motion of the dislocations.